THE EFFECT OF CLINICAL PATHWAY COMPLIANCE IN REDUCING LENGTH OF STAY - Michael Siswanto; Djazuly Chalidyanto (Indonesian Journal of Health Administration, 2020)
Background: Clinical pathway is multidisciplinary care plan based on the best clinical practice for a group of patients with a particular diagnosis, designed to minimize care delay as well as maximize the quality of care and clinical outcomes. In 2017, average length of stay for pediatric patient with acute gastroenteritis was prolonged even clinical pathways had been implemented.Aim: Thid study determined the diagnostic examination and therapy compliance of clinical pathway related to the length of stay.Method: This study was cross sectional research through simple random sampling. Researchers analyzed pediatric patients whose clinical pathway were filled completely by doctors. The inclusion criteria were pediatric patients, admitted to hospitals during January to December 2018 as acute gastroenteritis patients. The data were analyzed using multiple classification analysis.Results: There were 197 patients with clinical pathway filled completely. As much as 60.91% of cases were compiled for diagnostic examination and 88.32% for therapy. There was no statistically significant correlation between diagnostic examination compliance (p > 0.05) and therapy compliance (p > 0.05) of clinical pathway with patients’ length of stay (combined = p > 0.05).Conclusion: Many factors could be related with the length of stay especially patients’ condition itself. In this study, clinical pathway compliance has no impact in reducing length of stay. Keywords: clinical pathway, compliance, length of stay, pediatric.